2022
DOI: 10.1016/j.celrep.2021.110180
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar Typhimurium uses anaerobic respiration to overcome propionate-mediated colonization resistance

Abstract: Highlights d Nitrate-dependent anaerobic respiration enables propionate metabolism by S. Tm d Propionate metabolism supports S. Tm intestinal expansion in the inflamed gut d Propionate utilization by S. Tm is dependent on the SPI-1 effector SopE d Bacteroides-derived propionate fuels S.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…Interestingly, it has recently been shown that propionate metabolism is linked to intestinal expansion by S . Typhimurium in the inflamed gut (Shelton et al, 2022). Taken together, these findings suggest that independent mutations in barA and sirA acquired by late isolates in independent patients lead to largely (though not completely) overlapping transcriptomic changes, which include the downregulation of numerous SPI-1- and SPI-4-encoded factors and associated effectors.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has recently been shown that propionate metabolism is linked to intestinal expansion by S . Typhimurium in the inflamed gut (Shelton et al, 2022). Taken together, these findings suggest that independent mutations in barA and sirA acquired by late isolates in independent patients lead to largely (though not completely) overlapping transcriptomic changes, which include the downregulation of numerous SPI-1- and SPI-4-encoded factors and associated effectors.…”
Section: Resultsmentioning
confidence: 99%
“…The use of tetrathionate and nitrate as terminal electron acceptors allows Salmonella to use poorly fermentable carbon sources such as ethanolamine derived from enterocytes membrane; fructose-asparagine derived from host diet; and 1,2-propanediol, succinate, and propionate that are by-products of microbial fermentation [17,19,[93][94][95]. The exploitation of these carbon sources ensures a growth advantage over commensal bacteria, which solely rely on fermentation for growth [17,19,[93][94][95].…”
Section: Inflammation and The Newly Created Nichementioning
confidence: 99%
“…In addition, the gut microbiota protects the host by limiting enteric pathogen expansion (colonization resistance) partially via nutrient sequestration (Caballero-Flores et al, 2020; Krautkramer et al, 2021; Oliphant and Allen-Vercoe, 2019). Enteric pathogens, such as Salmonella enterica serovar Typhimurium ( S. Tm) and carcinogenic pks + Escherichia coli ( E. coli ) have evolved to overcome colonization resistance by inducing and/or thriving during intestinal inflammation (colitis) (Arthur and Jobin, 2013; Arthur et al, 2014; Bronner et al, 2018; Faber et al, 2017; Shelton et al, 2022; Thiennimitr et al, 2011; Zhu et al, 2019). One of the critical mechanisms driving a luminal expansion of pathogenic Enterobacteriaceae during colitis is the generation of respiratory electron acceptors as a byproduct of the inflammatory host response.…”
Section: Introductionmentioning
confidence: 99%